Facilitating blended learning by means of vidcasting - Storgaard, Carsten S.; Heilesen, Simon B. (Proceedings of the International Conference on Networked Learning, 2010)
ICT becoming ever more pervasive at universities, it is a challenge for educators to identify uses of technology that may enhance the learning experience rather than just remediate conventional teaching. Podcasting is a much acclaimed new technology. Although there is little hard evidence that the academic benefits of podcasts justifies the investment of resources, there are indications that podcasting 1) is being adopted by students as a supplementary study tool; 2) is considered by students to help improve the study environment; and 3) challenges faculty to reflect on and reconsider their teaching routines. This poster deals with A) experiences, from the point of view of the practitioner, with faculty use of the new technology, and B) the institutional and technical framework developed to support the use of podcasts in teaching. A) As to faculty use, we have observed that simply trying out the technology seems to foster creative ideas. One recent example involves replacing a long lecture on research methods with a series of short, thematic vidcasts. Small groups of students were assigned to watch and discuss the vidcasts constituting the lecture, and later each group was requested to present to the entire class the key points of their particular vidcast. In another course, a professor replaced in-class presentations of student group project proposals with short vidcasts recorded by each group. Thus valuable time was freed for more crucial teaching activities. It also turned out that the student presentations were better structured, more to the point, and more reflected than typical in-class presentations. B) Given that anyone with a minimum of technical skills can produce podcasts, and that faculty in general may be lacking skills to handle the technology and to make good presentations in the new medium, it is a challenge for university administrators to make available easy-to-use, efficient and cost-effective ICT-tools. Making sure that needs and not technology will be the driving force in this innovative process is an act of balance. At Roskilde University, policies and practices have been developed for augmenting academic activities on to the net by means of video podcasts. The principles underlying this development are: 1. Teaching and research communication in general are being viewed as two closely related aspects of audio-visual communication. 2. Adoption of net based audio-visual communication should be voluntary. 3. Production of vidcasts should be inexpensive and readily available.